SINERGI DESA ADAT DAN PENGELOLA PARIWISATA DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA PENGLIPURAN BANGLI - Libhi, Kadek Sidhi Surya; Mahagangga, I Gst. Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i02.p23, 2016)
This research is located at a Tourism Village Penglipuran, Bangli aims to determine the existing condition and synergy Desa Adat and Pengelola Pariwista Penglipuran in the development of tourism in Penglipuran Tourism Village, Bangli. Data collection techniques in this research are by observation, in-depth interviews, and study of the documentation relating to the secondary data in the field. The data have been obtained were analyzed by qualitative data analysis techniques that work with the data, organizing data, sorting them into manageable units, search and find patterns, find what is important, and what is learned, and deciding what can be describe to people other. Results of this study were concluded that the existing condition of Tourism Village Penglipuran includes, physical and non-physical condition. Synergies Desa Adat and Pengelola Pariwisata Penglipuran in the development of tourism at the Tourism Village Penglipuran is customary village as a tourism asset owners served as a maker and designer of the policy, while the tourism manager in charge of implementing the tourism policy. Moreover, in the management of the tourism activity undertaken by Pengelola Pariwisata, Desa Adat authorities to supervise all activities of tourism at the Tourism Village Penglipuran.
Keywords: Synergy, Desa Adat, Pengelola Pariwisata, Tourism Development, Tourism Village